Optimal Firm's Dividend and Capital Structure for Mean Reverting Profitability - Francesco Menoncin; Paolo Panteghini; Luca Regis (Center for Economic Studies and ifo Institute (CESifo), 2021)
We model a risk-averse firm owner who wants to maximize the intertemporal expected utility of firm's dividends. The optimal dynamic control problem is characterized by two stochastic state variables: the equity value, and profitability (ROA) of the _rm. According to the empirical evi-dence, we let profitability follow a mean reverting process. The problem is solved in a quasi-explicit form by computing both the optimal dividend and the optimal debt. Finally, we calibrate the model to actual US data and check both the properties of the solution and its sensitivity to the model parameters. In particular, our results show that the optimal dividend is smooth over time and that leverage is predominantly constant over time. Neither asymmetric information nor frictions are necessary to obtain these findings.
Keywords: H25; G32; G35; 330; dividend policy; capital structure; profit mean-reversion; closed-form; stochastic optimization